The influence of digital economy development on urban carbon emission intensity in the Yangtze River Economic Belt: Mediating mechanism and spatial effect - Ma, Lindong; Hong, Yuanxiao; He, Shouchao; Luo, Haibei; Liu, Guangming; Zheng, Jinhui; Xia, Yuntian; Xiao, Deheng (Frontiers in Ecology and Evolution, 2023)
The iterative upgrading of digital technology and the implementation of “carbon-peaking and carbon neutrality” national strategy provide an opportunity for the synergistic integration of digital economy and green economy in China, thus, whether the development of digital economy can curb urban carbon emission intensity (CEI) remains to be answered. Based on the panel data of 110 cities in the Yangtze River Economic Belt (YREB) region from 2011 to 2020, this paper investigated the impact of digital economy on CEI by using the dual fixed-effect model, the mediating mechanism model and the spatial Durbin model. The main results are as follows: (1) The development of digital economy in the YREB region can lower down CEI, promote the rationalization and upgrading of industrial structure, and improve cities’ green innovation capacity; (2) CEI was reduced through the intermediary effect of industrial structure optimization and upgrading and green technology innovation; (3) Digital economy shows a significant positive spatial correlation, and exerts a spatial spillover effect of reducing CEI in surrounding cities with obvious spatial heterogeneity; (4) Digital economy has a stronger inhibitory impact on CEI in the downstream cities and cities within the urban agglomerations; (5) In addition to digital infrastructure, the remaining components of digital economy, directly and indirectly, diminish CEI. At last, according to the research findings, suggestions for digital economy development in the YREB region are put forward.